Multi-stem mechanised harvesting operation analysis : application of discrete-event simulation - Hogg, Glynn A. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2009.